PLANTAS DEL CARBONÍFERO SUPERIOR DE LA QUEBRADA DE PASLEAM, PROVINCIA DE SAN JUAN, ARGENTINA (Ameghiniana, 2014)
Fossil plants of the NBG Zone (Late Carboniferous) have been recovered from the middle to upper section of the Tupe Formation at the Pasleam creek, San Juan province, Argentina. The species present are: Botrychiopsis weissiana Kurtz, Diplothmema bodenbenderi (Kurtz) Césari, Fedekurtzia argentina (Kurtz) Archangelsky, Nothorhacopteris argentinica (Geinitz) Archangelsky, and Paracalamites australis Rigby.